Mapping Research Dimensions of IJPER Journal (2008-2024): A Bibliometric Study Using Scopus Data - S, Madhu; H K, Pradeep; Sab M, Chaman (Journal of Data Science, Informetrics, and Citation Studies)
This bibliometric study assesses the research performance, collaboration patterns, and thematic evolution of the Indian Journal of Pharmaceutical Education and Research (IJPER) using Scopus data from 2008-2024. A total of 2,225 publications were analysed to evaluate growth trends, citation impact, authorship productivity, and institutional as well as international contributions. IJPER recorded a steady annual growth rate of 8.76%, with its most productive phase between 2016-2024 contributing 79.51% of total output. Collaborative authorship predominated (Degree of Collaboration=0.953), with three-authored papers accounting for 22.74% of publications. India contributed 1,599 papers (71.88%), followed by Saudi Arabia and Malaysia, indicating IJPER’s expanding international visibility. King Faisal University (221 papers) was the top contributing institution, and Nagaraja Sreeharsha was the most prolific author (42 papers). The most cited article (129 citations) focused on plant-based natural gums for novel drug delivery. Frequently used keywords antioxidant (62), validation (61), HPLC (54), and molecular docking (42) highlight the journal’s emphasis on analytical and formulation research. The study underscores IJPER’s growing scholarly influence and its significant role in fostering global collaboration and advancing pharmaceutical sciences.
Keywords: Bibliometric Mapping; Citation Analysis; Degree of Collaboration; Pharmaceutical Sciences; Scientometrics.